The streetlights are watching you: A historical perspective on value change and public lighting. (1st June 2022) - Stone, Taylor
Abstract : This article investigates questions of 'designing for value change' via a ubiquitous, yet often taken-for-granted, technology – streetlights. Smart city trends are spurring a new generation of streetlights, with lampposts being fitted with sensors, cameras and a host of other technologies aimed at monitoring and data collection. This has raised concerns about privacy, surveillance and power relations, arguably creating a changing value landscape for streetlights. However, the article will argue that, while smart streetlights may seem to instantiate a moment of value change, they in fact represent a continuity of values fundamental to the very foundations of public lighting. They embody a set of values – and value tensions – that can be traced back to the origins of modern public lighting in the seventeeth–eighteenth centuries. Moreover, urban nights occupy a liminal space at the boundaries of social order, which likewise informs streetlights' technical functions and symbolic meanings. Appreciating this continuity of values (and value tensions) is necessary for analysing the potential impacts of new innovations, as well as the value landscape that will inevitably shape their design and use. In adopting a historical perspective on a specific case study, as well as proposing the notion of value continuity, the article offers generalizable insights, as well as future research directions, for the theory and practice of designing for value change.